Is overactive bladder microvasculature disease a component of systemic atheroscleorosis?. Issue 4 (15th November 2017) - Yeniel, Ahmet Ozgur; Ergenoglu, Ahmet Mete; Meseri, Reci; Kismali, Erkan; Ari, Anıl; Kavukcu, Gulgun; Aydin, Hikmet H.; Ak, Handan; Atay, Sevcan; Itil, Ismail Mete
Abstract : Aims: To evaluate the relationship between overactive bladder (OAB) and systemic atherosclerosis in a cohort of women. Methods: In this case‐control study, we assessed atherosclerosis indicators, such as Framingham risk scores and carotid and femoral artery intima‐media thickness, and evaluated possible bladder wall responses to atherosclerosis using endovaginal color Doppler ultrasound and the detection of urinary cytokines in women with OAB and in controls. Quantitative assessment of blood perfusion at the bladder neck was performed using a method that allows for the dynamic monitoring of flow in a predefined region of interest at every point of the cardiac cycle. The independent samples t‐test was used to evaluate the relationship between OAB and the atherosclerotic findings when parametric conditions were met, and the Mann‐Whitney U test was used when parametric conditions were not met. Kendall's Tau was used to assess the correlation between OAB severity and the atherosclerotic variables. P < 0.05 was considered statistically significant. Results: There were 74 OAB patients and 73 controls; in total, 147 women were evaluated. We found that all atherosclerosis indicators were significantly associated with OAB and that there was a significant relationship between OAB and decreased bladder neck perfusion. Additionally, there were correlations of OAB severity with systemic atherosclerosis and impaired vascular perfusion of the bladder. Conclusions: Decreased perfusion at the bladder neck, the Framingham scores in severe OAB, and the correlation between them suggest that OAB microvascular disease may be a component of systemic atherosclerosis rather than a separate process.